transsib, bam, cer as flows - Grigoryeva , Elena; Lidin, Konstantin (project baikal, 2025)
Everyone knows the fate of cities bypassed by the main railway lines. Tyumen took away the palm from Tobolsk, Novosibirsk – from Tomsk. The once magnificent border town of Kyakhta and the capital Nerchinsk turned into mediocre settlements....The Baikal-Amur Mainline, the necessity of which was obvious to our great-great-grandfathers, made it possible to develop the riches of a large, once deserted, territory and populate it with new towns.The Chinese Eastern Railway – the southern branch of the great Trans-Siberian railway – gave another access to the ocean and promoted the development of the northern territories of China with a complex history, to which both our fatherland and Japan were related.Colleagues from the Pacific State University, students and followers of Nikolay Petrovich Kradin, consistently and methodically continue to accumulate the material on the ‘Russian East’. We hope that the descriptive set of data will lead them to deeper generalisations in the near future.
Keywords: Transsib; BAM; CER